Conversions to Catholicism among Fin de Siècle Writers: A Spiritual and Literary Genealogy - Claire Masurel-Murray (Cahiers Victoriens et Edouardiens)
During the last decade of the 19th century, a number of English writers converted to Roman Catholicism: the “Decadent” poets John Gray, Lionel Johnson and Ernest Dowson joined the Church in 1890 and 1891, while Oscar Wilde flirted with the Catholic faith during his college years at Oxford, and received the last sacraments on his deathbed in 1900. These writers all inherited from Walter Pater a taste for the splendours of religious rite. They were also influenced by their Pre-Raphaelite predecessors’ interest in the Catholic Middle Ages as well as by their emphasis on the aesthetic dimension of religious experience, and claimed their kinship with the art for art’s sake creed of French Parnassians and Symbolists (Gray, in particular, translated several of Verlaine’s Catholic poems). The Decadent converts were also marked by another major, but less obvious, imprint, that left by John Henry Newman. The Tractarian theologian’s religion may at first sight have little in common with the aesthetic religion of the fin de siècle poets, and yet his view of the act of faith as founded on the senses, the emotions and the imagination was certainly an element that they were keen to appropriate, and his focus on the human conscience as the centre of religious experience is implicitly present in the solitary and highly subjective piety that emerges in the works of Gray, Johnson and Dowson.